The Effect of Differences in Closed House Density on the Outlet Near Zone on the Finisher Phase Broiler Performance - Nilawati Widjaya; Sari Suryanah; Tedi Akhdiat; Hilman Permana; Raden Febrianto Christi; Munajat Yulianto (Bantara Journal of Animal Science, 2022)
Research on the Effect of Differences in Density of Closed House Cages in the Zone Near Outlet on Broiler Performance in the Finisher Phase, has been carried out for 40 days, from May 25, 2021 to July 3, 2021. The study was conducted at Farm H. Noto Miharjo Adiwarno Village, Buayan District, Kebumen Regency, Central Java. This study aims to determine the effect of differences in cage density in the zone near the outlet in the closed house cage on the performance of the finisher phase broiler chickens and to find out how much the density of the cage in the zone near the outlet in the closed house cage is capable of producing optimal finisher phase broiler performance. This research was conducted using the Experimental Method. The design used was a completely randomized design (CRD), which consisted of 4 treatments, namely P0 (cage density 10 birds/meter2), P1 (cage density 12 birds/meter2), P2 (cage density 14 birds/meter2), and P3 (cage density 14 birds/meter2). cage 16 tails/meter2). Each treatment was repeated 5 times, and each replication consisted of a different number of boilers according to the density of the cage used. The observed variables were feed intake, daily weight gain and feed conversion. The data obtained were analyzed using variance, if there was an effect of treatment followed by Duncan's multiple area test. The conclusion of this study was the difference in density of closed house cages in the zone near the outlet had a significant effect on daily body weight gain, but had no significant effect on ration consumption and feed conversion. The cage density of 12 birds/meter2 can produce optimal body weight gain.Keywords: Closed house, outlet, broiler, feed consumption, body weight gain, feed conversion.